2016
DOI: 10.1017/s1431927616000520
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Noninhibitory Serpin Maspin on the Actin Cytoskeleton: A Quantitative Image Modeling Approach

Abstract: Image analysis results showed that the effects of maspin were mirrored by effects on cell architecture, in a way that could be described quantitatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The method integrated two texture analysis methods: GLH and GLCM to find some important information about the shape and behavior of the ruffling region. This paper differs from the previous model developed by Al-Mamun et al, (2016b) in various ways.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…The method integrated two texture analysis methods: GLH and GLCM to find some important information about the shape and behavior of the ruffling region. This paper differs from the previous model developed by Al-Mamun et al, (2016b) in various ways.…”
Section: Discussionmentioning
confidence: 74%
“…In a recent attempt, Al-Mamun et al, (2016b) showed that an image processing tool can be used to quantify three cellular parts: nuclei, cytoplasm and ruffling regions to observe the changes in shape and behavior. The study considers descriptors including area, perimeter, integrated optical density, fractal dimension and circularity to quantify each cellular part.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations